Fish, Freshwater, and the Promise of Biodiversity History for Indonesian Studies - Medrano, Anthony D. (Forest and Society, 2023)
Freshwater fishes abound in Indonesia. They are everywhere in the archipelago—from rice fields and irrigation canals to brackish lagoons and highland rivers. They even populate the most unassuming bodies of water. Some species are found in the remotest of volcanic lakes while others call the blackest and most acidic peat swamps their home. Every island has its habitats and every habitat has its fishes, making Indonesia one of the world’s richest centers of ichthyofauna diversity. And yet, thinking with freshwater fishes—and their biodiversity history—has been largely absent from the field of Indonesian studies. A telling example of this biological blindspot can be found in the ways in which the Cornell Modern Indonesia Project (CMIP) has produced—and continues to constitute—Indonesia as an area of study and attachment. In CMIP’s Producing Indonesia: The State of the Field of Indonesian Studies, a landmark volume published in 2014, there were twenty-seven contributions that spanned the humanities and social sciences but none that looked at the role local scientists played in knowing the archipelago’s freshwater fauna or even broader the interplay between environment and society in shaping the study of modern Indonesia. In response, this essay centers the interplay between environment and society to show how it can open up new directions for future research and interdisciplinary collaboration. In doing so, and in particular, the paper argues that the story of fish and freshwater illustrates the promise of biodiversity history for the field of Indonesian studies in the age of environmental humanities and beyond.